Ensuring the sustainability of Economic Growth: Avoiding the Mexican Experience - Congressional Planning and Budget Office, CPBO - (Kasarinlan: Philippine Journal of Third World Studies, 2008)
Mexico paid the price for its complacency; the Mexican monetary crisis occurred because it failed to address basic weaknesses in its economy, such as low domestic savings mobilization rate, high trade and current account deficits, currency overvaluation, excessive dependence on foreign money - traits Mexico shares with the Philippines. This paper paints the Mexican crisis as a cautionary tale for the Philippines. It points to the ability of the government to manage monetary policy competently, particularly as they affect exchange rates, as the most crucial to the sustainability of economic growth. Secondly, it shows how strong and convincing measures to mobilize domestic savings need to be undertaken in order to show the investing community that the Philippines has the resolve to reduce its dependence on foreign capital.